An APOBEC Cytidine Deaminase Mutagenesis Pattern is Widespread in Human Cancers - Roberts, Steven A. (2013)
Recent studies indicate that a subclass of APOBEC cytidine deaminases, which convert cytosine to uracil during RNA editing and retrovirus or retrotransposon restriction, may induce mutation clusters in human tumors. We show here that throughout cancer genomes APOBEC mutagenesis is pervasive and correlates with APOBEC mRNA levels. Mutation clusters in whole-genome and exome datasets conformed to stringent criteria indicative of an APOBEC mutation pattern. Applying these criteria to 954,247 mutations in 2,680 exomes of 14 cancer types, mostly from TCGA, revealed significant presence of the APOBEC mutation pattern in bladder, cervical, breast, head and neck and lung cancers, reaching 68% of all mutations in some samples. Within breast cancer, the HER2E subtype was clearly enriched with tumors displaying the APOBEC mutation pattern, suggesting this type of mutagenesis is functionally linked with cancer development. The APOBEC mutation pattern also extended to cancer-associated genes, implying that ubiquitous APOBEC mutagenesis is carcinogenic.